Diplomatic Privileges in Dispute: A Legal-Political Analysis of Indonesia's Strategic Compliance with the Vienna Convention - Iskandarsyah, Muhammad Raditya; Zaky Ismail (Department of International Relations, Brawijaya University, 2025)
This research is important because the 1961 Vienna Convention is a key instrument of international law governing diplomatic relations, while Indonesia, as a state party, faces challenges in implementing its principles amid local political dynamics and demands for national sovereignty. The research aims to analyse the implementation of the principles of the 1961 Vienna Convention in the provision of diplomatic facilities in Indonesia, identify the legal-political factors that encourage/inhibit, and examine the gap between international norms and field practices. The method used is a normative-qualitative study with analysis of legal documents, national regulations, and practical cases to explore the gap between normative ideals and implementation reality. The results, analysed through the lens of Liberal Institutionalism, show that although the core principles of the Vienna Convention are formally adopted, various cases of misuse of diplomatic facilities by foreign missions indicate selective compliance by Indonesia driven by legal and political calculations. In conclusion, Indonesia's commitment to the 1961 Vienna Convention is dualistic: on the one hand, it adheres to the basic principles to maintain international reputation (in line with the assumption of institutional cooperation), but on the other hand, it is flexible through legal-political grey spaces to protect national sovereignty and interests, revealing the complexity of the interaction between international norms and realpolitik.